The relationship between perfectionism and psychopathology: a meta-analysis - Limburg, K.; Watson, H.; Hagger, Martin; Egan, Sarah (John Wiley & Sons, 2016)
Objective: The clinical significance of 2 main dimensions of perfectionism (perfectionistic strivings and perfectionistic concerns) was examined via a meta-analysis of studies investigating perfectionism in the psychopathology literature. Method: We investigated relationships between psychopathology outcomes (clinical diagnoses of depression, anxiety disorders, obsessive-compulsive disorder, and eating disorders; symptoms of these disorders; and outcomes related to psychopathology, such as deliberate self-harm, suicidal ideation, and general distress) and each perfectionism dimension. The relationships were examined by evaluating (a) differences in the magnitude of association of the 2 perfectionism dimensions with psychopathology outcomes and (b) subscales of 2 common measures of perfectionism. Results: A systematic literature search retrieved 284 relevant studies, resulting in 2,047 effect sizes that were analysed with meta-analysis and meta-regression while accounting for data dependencies. Conclusion: Findings support the notion of perfectionism as a transdiagnostic factor by demonstrating that both dimensions are associated with various forms of psychopathology.